Sleep bruxism and mouth breathing: a new approach - Herrera López, Isis Bárbara (2018)
The sleep bruxism is an involuntary habit, also called parafunction, which occurs as the body’s response to several associated factors. More than 20% of the world population is affected by this; without predilection for age or sex, although peaks may occur in stages of life such as adolescence and adulthood. It produces sequels in the stomatognathic apparatus as well as the rest of the body. The sleep bruxism is a type of bruxism, difficult to diagnose since sophisticated and expensive equipment is needed, also because the patient is not aware of what he is doing; therefore, this makes its control and treatment more complicated. In recent research it is said that the habit of mouth breathing could trigger the sleep bruxism and/or increase the seriousness of its effects. Not all patients with sleep bruxism necessarily have the habit of mouth breathing, but all patients with the habit of mouth breathing have episodes of sleep bruxism. Because of the detriment of this parafunction and the damage it causes to the organism, affecting the quality of life, and due to the little knowledge about the relationship between both entities, a literature review was carried out with the objective of collecting updated information about the habit of mouth breathing as a possible trigger factor of sleep bruxism.